PENETRATING CRANIUM INJURY BY A CONCRETE NAIL: CASE STUDY - Al-Turki, Ali Ali; Siamionau, Viachaslau V.; Tsiatsiuyeu, Andrei M. (Universal Journal of Pharmaceutical Research, 2024)
The article describes a case study, demonstrating the infliction of a single blind penetrating «gunshot» wound to the head with a concrete nail fired from a powder-actuated fastening tool. Forensic examination of the injury caused by atypical projectiles when fired from atypical firearms can be a difficult task. The results of a thorough autopsy examination of the body and the ante-/post-mortem discovery of atypical projectiles (or other foreign objects) in the victim’s body are the prerequisite for correct interpretation of the injury morphological features. Peer Review History: Received: 2 October 2023; Revised: 5 November; Accepted: 26 December; Available online: 15 January 2024 Academic Editor: Dr. Muhammad Zahid Iqbal , AIMST University, Malaysia, drmmziqbal@gmail.com Reviewers: Dr. Rima Benatoui, Applied Neuroendocrinology Laboratory, Faculty of Sciences, University of Annaba, Algeria. benattouiryma@gmail.com Dr. Owanaro Peter, Nigeria, Department of Clinical Pharmacy and Pharmacy Practice, Faculty of Pharmacy, Niger Delta University, Wilberforce Island, Bayelsa State, Nigeria. owonaropeter@gmail.com